Relationship of Bullying with psychological security and Self-Esteem among a sample of first year students at Tabuk University in Tabuk - Alodhayyani, Joud Masad; Alhomidi, Ahmed Ali (Journal of Educational and Psychological Sciences, 2025)
The study aimed to investigate the nature of the relationship between bullying, psychological security, and self-esteem among a sample of first-year female students at the University of Tabuk in the Kingdom of Saudi Arabia. The correlational descriptive approach was employed, and the instruments included the Bullying Victim Scale developed by Mas'ad Abu Al-Diyar (Jueijea, 2017), the ISBI Self-Esteem Scale (Helmreich et al., 1995), and Maslow’s Psychological Security Scale (Al-Oqaili, 2004). These tools were administered to a sample of 77 female students aged between 18 and 21 years. The results indicated that the prevalence level of bullying among the sample was low. Moreover, the findings revealed no statistically significant relationship between bullying and psychological security, nor between bullying and self-esteem. However, a statistically significant relationship was found between psychological security and self-esteem. Based on these findings, the study recommended raising students' awareness of the concept of psychological security and its impact on mental health, normalizing the existence of bullying among adults to challenge feelings of social stigma, and emphasized the importance of the presence of psychological and social counselors in universities and other educational institutions to provide psychological and social support.
Keywords: Self-Esteem; Psychological security; Bullying; preparatory year students at the University of Tabuk